Infección del tracto urinario en el embarazo: Diagnostico clínico asociado a las pruebas Microbiológicas (urocultivo – antibiograma) en Gestantes atendidas en el Hospital Minsa II – 2 Tarapoto, periodo 2014 - Cárdenas Guerra, Gavino (2016)
The following research "Urinary tract infection in pregnancy: clinical diagnosis Associated with microbiological tests (urine culture - susceptibility) in pregnant Women at the MINSA II - 2 Tarapoto Hospital, 2014 period", it is a not Experimental, quantitative, descriptive, retrospective correlational study, whose Objective was to determine the association of microbiological clinical diagnostic Tests (urine culture - antibiograma) for the detection of urinary tract infection in Pregnant women at the Tarapoto Health Hospital II - 2, 2014 period; whose Sample was 75 medical records of pregnant women, the methodology was Reviewing medical records and record data collection instrument. The results were: the proportion of urinary tract infection (UTI) by clinical Diagnosis was the result of positive urine culture is 26.7% (20) women. By type Of clinical diagnosis 88.0% presented supra pubic pelvic pain, dysuria 65.3% and Lumbar pain, fever 58.7%, 52.0% positive ipsilateral lumbar fist percussion. 68.0% Had complete urine test with more than 5 erythrocytes and leukocytes 89.3% in October. 14.7% had positive culture in three stages. The ITU was as pathogens: Escherichia coli 80.0%, 10.0% Enterobacter spp, 5% had klebselia ssp. The ITU As antibiotic resistance was to: AC_Nalidixico, amoxicillin, ampicillin, ampicillin Sulbactam, amox./Ac clavulinic, ciprofloxacin. The association between the type Of pathogen from the urine culture with antibiogram was: Cefalotina (X2 = 15,417 And p = 0.017), Cefataxime (X2 = 18,980 and p = 0.004) and imipenem (X2 = 13,000 and p = 0.043). In conclusion there is an association between clinical diagnosis and Microbiological tests in 26.6% of cases. Keywords: urinary tract infection, clinical diagnosis, microbiological tests, urine Culture, antimicrobial susceptibility